Characterisation of porous solids V : proceedings of the 5th International Symposium on the Characterisation of Porous Solids (COPS-V), Heidelberg, Germany, May 30-June 2, 1999 /: proceedings of the 5th International Symposium on the Characterisation of Porous Solids (COPS-V), Heidelberg, Germany, May 30-June 2, 1999. (2000) - Unknown
No abstract available